Epidemiological Research: Terms and Concepts - Miettinen, O. S. (Springer, 2011)
In his The Joys of Yiddish (1970), Leo Rosten delights the reader with this vignette: A bright young chachem told his grandmother that he was going to be a Doctor of Philosophy. She smiled proudly: ‘Wonderful. But what kind of disease is philosophy?’ The reader here might wonder what a chachem is, but not after reading Rosten: it’s a great scholar, a clever and wise learned person. On the other hand, though, the reader here, like that grandmother, likely presumes to know what a doctor and a disease are; but (s)he might do well consulting a suitable source on this too – a contemporary medical dictionary won’t do (cf. sect. I – 1. 1 here) – insofar as (s)he is enough of a chachem to really care about the meanings (s)he associates with words. According to The American Heritage Dictionary of the English Language, a dictionary is, in one of the four meanings of the word, “A book listing words or other linguistic items in a particular category of subject with specialized information about them: a medical dictionary.” The listing generally is alphabetical in its ordering. This book is, mainly, a dictionary in that meaning, with terms of American English – and some of their initials-based abbreviations also – addressed in alphabetical order; but it also is designed – by the proposed selection from among the terms and the proposed ordering of these – to function as a textbook in an introductory course on epidemiological research (see Introduction below). A term is, in logic and also in that word’s usage here, a word or a composite of words – such as ‘epidemiological research’ – that can be the subject or predicate of a proposition [1]. The “specialized information” that this book gives about the terms it covers is their meanings, that is, the concepts to which they refer. This information is, in part, merely descriptive of prevailing terms and the concepts to which they refer; but it commonly also is quasi-prescriptive, conveying my opinion of what the term or the concept, or both, ought to be. A concept is the essence of a thing (entity, quality/quantity, relation); it is true of every instance of the thing and unique to it [1].